TOURISM IMPACT ON SOCIAL CULTURE COMMUNITY IN THE NUSA PENID TOURISM AREA - Sudipa, Nyoman; Mahendra, Made Sudiana; Adnyana, Wayan Sandi; Pujaastawa, Ida Bagus (E-Journal of Cultural Studies; Volume 13, Number 3, August 2020, 2020)
The growth of tourism in the Nusa Penida Tourism Area has an impact on the socio-cultural environment due to the development of tourism supporting facilities and infrastructure. Socio-cultural spaces also experience pressure due to conflicts of interest in the use of sacred areas for tourism, resulting in a process of desacralization. Social interactions are declining and arrogance is increasing at some tourist attraction points. Some physical spaces have become economic spaces. Road border, roadside, coast have become economic space. The way of thinking has been hegemony by the interests to get more economic access. The construction of the mind is filled with capitalist desires. Arrogance and ego between groups began to be seen in each particular area. The narrowing of social and cultural space has increased the critical power of the community towards the use of the area, especially spaces that are related to religion. Fighting egoism and social cultural conflict to catch up with the material culture. The social and cultural life of the Nusa Penida people is forced to adapt to material cultures. So fast tourism to Nusa Penida leaves the mindset, knowledge and culture that has been developing in the Nusa Penida community. Keywords: impact, social, culture, tourism, nusa penida